Durability of Photosensitizers in a Photo-oxidation Reaction in a Novel Oscillatory Baffled Photo Reactor - Jianhan Chen; Rohen Prinsloo; Xiongwei Ni (Georg Thieme Verlag KG, 2023)
With the rapid development of novel photosensitizers/photocatalysts, photochemical transformation has become possible and practical. In this context, we report for the first time our work on testing and quantifying the durability and robustness of a heterogeneous photosensitizer, polymer-supported rose Bengal (Ps-RB) beads, in a model photo-oxidation reaction between α-terpinene and singlet oxygen (1O2). A novel photo reactor is used due to its capabilities of providing uniform suspensions of solid beads and uniform light distribution. We have proposed a methodology for quantifying the durability of the beads including the factors of loss of beads and the reduced product concentration. The results show that the durability of the Ps-RB beads has decreased by about 67% after five consecutive runs, and the half-life of the beads can be reached in less than 200 minutes. In addition, we have also identified the optimal bead mass in the novel photo reactor. Our work not only enriches the designs of new and better photosensitizers but also provides a comprehensive methodology for testing and validating photosensitizers.